Peramalan Jumlah Penumpang Kapal di Pelabuhan Pantai Baru dengan Metode Sarima Dan Winter’s Exponential Smoothing - Ribowo Inmas Puja Negara (Badan Pusat Statistik Provinsi NTT, 2021)
Abstract This paper discusses the modeling of the number of ship passengers at Pantai Baru Port, Rote Ndao Regency. The number of ship passengers always change fluctuately every year and tends to be more stable than other modes of transportation such as fast boats at Ba'a Port and planes, especially during the Covid-19 pandemic. Therefore it is necessary to predict the number of passengers in the future to help the government to determine policies and maintain health protocols at Pantai Baru port, and to help in providing swab and rapid test kits for passengers, also help ship managers to determine the number of ships’ activity at Pantai Baru port so as not to suffer losses if number of passengers loaded does not meet the minimum travel costs. Forecasting number of passengers is done by choosing the best method between the Seasonal Autoregressive Integrated Moving Average (SARIMA) model and Winter's Exponential Smoothing model because it is indicated that the number of ship passengers is influenced by data trends and seasonal patterns. The best SARIMA method obtained is SARIMA (1,1,1)(0,1,1)12 and best Winter's Exponential Smoothing method is the multiplicative model with alpha 0.8, beta 0.1, and gamma 0.1 . Based on the MSE comparison value, SARIMA (1,1,1)(0,1,1)12 is more suitable for predicting the number of ship passengers at Pantai Baru Port. With the results of this forecast, hope it can help the government of Rote Ndao Regency and the managers of ships at Pantai Baru Port determine policies, especially during this pandemic.